Perceptual cues of stop consonants in kannada - S.R. Savithri, H.S. Sridevi (Journal of All India Institute of Speech and Hearing, 1970)
The aim of this project is to extract the perceptual cues of stop consonants in Kannada.The stop consonants were considered due to their special nature.The phonetic environment of the 12 stops (k, kh, g, gh, t, th, d, dh, p, ph, b, bh) and 4 affricates (c, ch, j, jh) were determined on the basis of results of a pilot study. 553 meaningful words with these stops were considered under 3 conditions namely preceding vowel and following vowel and consonant condition. All these wordsembedded in the sentence "WORD" anta he:lti:ni" formed the stimuli.